Multimodal Critical Discourse Analysis to Argumentative Essay Writing Skill Develop - Ade Elvira; Fera Zasrianita; Andriadi Andriadi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Argumentative essay writing is essential for developing students’ critical thinking, analytical reasoning, and persuasive communication. However, many learners struggle to construct coherent arguments, integrate evidence effectively, and sustain logical flow. This study examines the potential of Multimodal Critical Discourse Analysis (MCDA) as a pedagogical tool to improve argumentative essay writing skills. MCDA focuses on the interaction of linguistic, visual, and auditory modes in shaping meaning, enabling students to critically analyze multimodal sources such as films, advertisements, and digital media. Through classroom observations, interviews, and writing evaluations, the study found that MCDA encourages deeper engagement with complex issues and promotes critical interpretation beyond surface-level description. Students became more aware of how multimodal elements influence meaning, leading to improved ability in building evidence-based arguments. The approach also increased motivation, as learners worked with authentic, culturally relevant materials. While some students initially faced challenges in interpreting multimodal data, targeted scaffolding supported their progress. Overall, integrating MCDA into writing instruction not only strengthened students’ argumentative structures but also enhanced their critical literacy. This research highlights MCDA as an effective method for linking multimodal analysis with academic writing, preparing learners to navigate diverse discourse environments in the modern era.